Modeling and design of Galfenol unimorph energy harvesters. (5th November 2015) - Deng, Zhangxian; Dapino, Marcelo J
Abstract: This article investigates the modeling and design of vibration energy harvesters that utilize iron-gallium (Galfenol) as a magnetoelastic transducer. Galfenol unimorphs are of particular interest; however, advanced models and design tools are lacking for these devices. Experimental measurements are presented for various unimorph beam geometries. A maximum average power density of 24.4 and peak power density of 63.6 are observed. A modeling framework with fully coupled magnetoelastic dynamics, formulated as a 2D finite element model, and lumped-parameter electrical dynamics is presented and validated. A comprehensive parametric study considering pickup coil dimensions, beam thickness ratio, tip mass, bias magnet location, and remanent flux density (supplied by bias magnets) is developed for a 200 Hz, 9.8 amplitude harmonic base excitation. For the set of optimal parameters, the maximum average power density and peak power density computed by the model are 28.1 and 97.6 respectively.